PENGARUH NILAI KURS (USD) DAN VOLUME PERDAGANGAN SAHAM TERHADAP HARGA SAHAM PADA PERUSAHAAN BANK BUMN YANG GO PUBLIC DI BURSA EFEK INDONESIA TAHUN 2010 s/d 2014 - Rizky, Aznedra (JURNAL DIMENSI, 2015)
From the year 2010 until 2014, the domestic currency (rupiah) declined against the US dollar is unstable, affecting the company's stock price at the state-owned banks to go public on the stock exchange Indonesia.This study was conducted to determine the effect of exchange rate value (USD) and the volume of shares trading on the stock price on the company's state-owned banks to go public on the stock exchanges in Indonesia empirical study period 2010 s/d 2014. This study uses data sequence (time series ) for a period of 5 years and the sample used is enterprise state-owned banks to go public on the Indonesian stock exchange that consists of only four banks, namely Bank Mandiri (BMRI), BRI (BBRI), BNI (BBNI), and BTN (BBTN). Sampling method used is purposive sampling method, while analysis in this research is descriptive analysis, the classical assumption test, multiple linear regression, t-test, f, and the coefficient of determination.            The results obtained in this study is a t test on the value of exchange rates (USD) has sig a, that is 0.000 0.05, which means the value of exchange rates (USD) significantly influence the share price. While the t-test on stock trading volume has sig a, namely 0.552 0.05, which means the volume of stock trading has no significant effect on the share price. In test F sig 0,000 less than 0.05, which means that the variable value of exchange rates (USD) and the volume of stock trading is jointly have a significant influence on the share price. Determination coefficient of 0.456 or 45.6 % shows that the percentage contribution of the variable value of exchange rates (USD) and the volume of shares trading on the stock price by 45.6 % while the remaining 54.4 % is influenced by other factors.